Comparison of acute phase reactant levels of Kawasaki disease patients who visited with less than 5 days duration of fever and with 5 days or longer - Hyun Jeong Do; Jin Hee Jeong; Dong Hoon Kim; Tae Yun Kim; Changwoo Kang; Soo Hoon Lee; Sang Bong Lee (Pediatric Emergency Medicine Journal, 2019)
Purpose Kawasaki disease (KD) is a common, acute systemic vasculitis in children. Acute phase reactants (APRs) have been used to assist diagnosis, and to predict outcome in children with KD. However, it remains unknown on levels of APRs depending on duration of fever. We aimed to compare APR levels of children with KD who visited with < 5 days duration of fever and with ≥ 5 days. Methods Children (≤ 15 years) with complete KD who visited the emergency department were enrolled from March 2012 through February 2018. The children were divided into the early (fever < 5 days) and late (fever ≥ 5 days) presenters. The baseline characteristics, APR levels, such as platelet count, and outcomes were compared between the 2 groups. Results A total of 145 children with complete KD were enrolled. Median age was 27.0 (interquartile range [IQR], 12.0-46.5) months, and boys accounted for 60.0%. The early presenters (63 [43.4%]) had a younger age (17.0 [IQR, 7.0-45.0] vs. 32.5 [IQR, 14.0-48.0] months; P = 0.006), shorter duration of fever (3.0 [IQR, 2.0-4.0] days vs. 6.0 [IQR, 5.0-7.0] days; P < 0.001), and a lower platelet count (336.7 ± 105.2 [× 103/μL] vs. 381.6 ± 121.8 [× 103/μL], P = 0.02) than the late presenters. The other APR levels, and frequency of resistance to intravenous immunoglobulin and coronary artery abnormalities showed no differences between the 2 groups. Conclusion Children with KD who visited with < 5 days duration of fever had a lower platelet count compared to those with ≥ 5 days. No differences were found in the other APR levels and the outcomes. It may be necessary to consider the differences in APR levels depending on duration of fever when treating children with KD.